Philippines : 2008 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Philippines. (IMF Staff Country Reports; Country Report, 2009)
The staff report for the Philippines' 2008 Article IV Consultation is focused on economic developments and policies. A deepening of the global economic downturn presents downside risks to this outlook. Inflation is expected to reach 9 1\2 percent in 2008 and decline to 6 percent in 2009, led by a decline in commodity prices and weaker demand. Bank surveillance has been strengthened and steps have been taken to reduce risks related to off-balance sheet activities.